PENGEMBANGAN HANDOUT BERBASIS GUIDED NOTE TAKING PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Neti Diana; Sugeng Sutiarso; Haninda Bharata (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This study aims to develop teaching materials in the form of handouts based on Guided Note Taking on the system material of three-variable linear equations and to determine the quality of handouts in terms of validity and practicality. This research is a development research that refers to the 4D development model namely define, design, develop, disseminate. The subjects in this study were 2 teachers and 5 students of SMA Negeri 1 Buay Bahuga. The instruments used to measure the quality of the handouts developed included expert questionnaires, teacher and student response questionnaires. Expert questionnaires were used to measure the validity of the handouts, while teacher and student response questionnaires were used to measure the practicality of the handouts. The research product was a handout based on Guided Note Taking on the material of the system of linear equations of three variables for class X SMA. The results showed that from the aspect of validity it was included in the valid category with an average score of 75 based on the assessment of two expert lecturers (material, design and language experts); of the two teachers' responses with an average of 42.5 were in the good category and the student responses with an average of 41.8 were in the good category so that the practicality aspect was categorized as practical based on the results of the handout user's response. Based on the research results, it can be concluded that the handout based on guidance notes on the material for the three-variable linear equation system developed is valid and can be used practically in learning.